From “Non-encounters” to autonomic agency. Conceptions of patients with low back pain about their encounters in the health care system - Holopainen, R.; Piirainen, A.; Heinonen, A.; Karppinen, J.; O'Sullivan, Peter (2018)
Low back pain is a considerable health problem which affects people around the world, causing major healthcare costs. The use of qualitative research methods enables us to describe and understand patients’ experience of, and attitudes to, healthcare. The aim of the present phenomenographic study was to identify and describe the contextual nature of the conceptions of patients with low back pain of their encounters in the HCS. Seventeen patients with chronic or episodic low back pain classified as “high risk” were interviewed in open recall interviews, using videos of patients’ initial physiotherapy sessions that had been recorded previously. The data were analysed using the phenomenographic method. Patients’ conceptions of their clinical journey were formulated by a variety of themes: convincing care, lifestyle change, participation, reciprocality and ethicality of encounters. The themes varied in four categories: “non-encounters”, seeking support, empowering collaboration and autonomic agency. The results showed a range of clinical interactions – from very negative and disempowering, to empowering and life changing. The key differences between the first and second categories were professionals “being present” and patients starting to understand their low back pain. Between the second and third category, the key aspects were strong therapeutic alliance and the active participation of the patient. Finally, the key differences between the third and fourth categories were the patient being in charge and taking responsibility while knowing that help was available if required. The results may help in improving the care of patients with low back pain.